Just transitions for a Climate-Resilient Development in Africa – Transforming Dialogue into Action - African Union Commission; United Nations Economic Commission for Africa; African Development Bank; Government of Namibia; Pan African Climate Justice Alliance; African Chicken Genetic Gains; African Centre of Meteorological Application for Development; International Livestock Research Institute; Food, Agriculture and Natural Resources Policy Analysis Network; Deutsche Gesellschaft für Internationale Zusammenarbeit; International Union for Conservation of Nature; Southern African Science Service Centre for Climate Change and Adaptive Land Management; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
CCDA-X1, hosted by the Government of Namibia, convened on the theme: “Just transitions for a Climate-Resilient Development in Africa – Transforming Dialogue into Action” in collaboration with Africa’s civil society organisations, academia, development partners, regional and international organisations and the private sector. The conference resulted in the following key messages to be taken forward to COP27 by Namibia.